Land use/land cover dynamics, trade-offs and implications on tropical inland shallow lakes' ecosystems' management: Case of Lake Malombe, Malawi. Issue 1 (1st January 2021) - Makwinja, Rodgers; Mengistou, Seyoum; Kaunda, Emmanuel; Alamirew, Tena
ABSTRACT: Lake Malombe supports various ecosystem services (ESs). However, it is increasingly experiencing human-induced pressure. This study used geospatial, household surveys, focus group discussion, key informant interviews, consultative meetings, and field observation on assessing the Land use/Land cover dynamics (LULCD), its trade-offs, and implications on ESs. The findings demonstrated a decrease in forest land (52, 932 ha to 78, 983 ha) at the expense of cultivated (52, 932 ha to 78, 983 ha) and settlements (7054 ha to 17, 595 ha). Changes in ecological indicators such as fishery, river flow, soil erosion, turbidity, biodiversity, invasion of alien species, scenic beauty, extinction of some species, frequent flooding, cultural value, and carbon sequestration were significantly (p-<0.05) linked to some LULCD classes. The study findings are significant to policymakers, ecosystem managers, the local population, and various stakeholders in understanding conflicting interests and policy priorities to balance the lake ecological restoration and human welfare.